k 0-INAA as a contributor in nutrition and health: multielemental determination in Stevia rebaudiana Bertoni, leaves and stevioside product - Bedregal, P.S. (2018)
Concerned about food safety and considering the advantages that bring the use of the powerful INAA technique based in k0 method, we have decided to perform a complete multi element determination in the leaves and in the product stevioside, of Stevia rebaudiana Bertoni, which use as a sweetener has increased in the last decade. Using Stevia leaves from different origin, thirty seven elements were determined using k0-INAA; copper was quantified using FAAS, while sixteen elements were determined in the stevioside product from different manufacturers. The results indicated that it is necessary to make a strict quality control on the content of elements in leaves, which are used both as a raw material of the stevioside product, as a sweetener.